Olfactory Recovery After Endoscopic Endonasal Transsphenoidal Surgery for Pituitary Lesions : A Comprehensive Study - Li Yun, Lim; Paul Patrick, Berundang; Ing Ping, Tang (Turkish Rhinology Society, 2025)
Objective: The aim of this study was to evaluate the olfactory outcome in pituitary lesions after endoscopic endonasal trans sphenoidal surgery. Methods: In this prospective study, the olfactory function of patients was assessed subjectively using visual analog scale (VAS) and objectively using “Smell and Scratch” smell test kit before surgery, followed by 6 weeks and 6 months after surgery. Results: Fourteen patients were included in this study, with 57% females and 43% males. The average age of the patients was 56.4 years. Thirteen cases were pituitary adenoma and 1 case was pituicytoma, while 64% were nonsecreting tumors and 36% secreting type. The average tumor diameter operated on was 24.14 mm with 70% showing suprasellar extension. Nine cases had intraoperative cerebrospinal !uid leaks, which were repaired with nasoseptal !aps. Smell test kit results showed no changes in smell test kit scores across 3 time points: pre-surgery, 6 weeks postsurgery, and 6 months post-surgery (P = .29). However, patients’ perception of olfaction was signi"cantly reduced using the VAS score pre-surgery and 6-weeks post-surgery (Z=!2.75, P = .006) while improved signi"cantly from 6 weeks post-surgery to 6-months post-surgery (Z=!2.49, P = .01). No statistical significance in smell test kit score and VAS score differences was seen in different age groups, genders, tumor types and location, and !ap usage intraoperatively. Conclusion: Olfactory outcomes post-surgery showed no signi"cant changes objectively, but subjectively, patient’s olfaction, evaluated with VAS, had shown notable effects.